Knowledge, Economic Growth and the Role of Policy : On the Role of "Public-Private Partnerships" in the new "Knowledge-Driven" Economy.: On the Role of "Public-Private Partnerships" in the new "Knowledge-Driven" Economy. (2000) - Unknown
No abstract available